Impact of land prices on corporate carbon emission intensity - Lin Guo; Ying Liu; Zeqing Jiang; Xiaoping Yuan; Qi Jing (Scientific Reports)
Abstract This study examines the impact of micro-level land prices on corporate carbon emission intensity and identifies the underlying mechanisms. Using a unique dataset of Chinese industrial enterprises from 2000 to 2014, we employ a two-way fixed effects econometric model, alongside instrumental variable and Difference-in-Differences (DID) techniques, to address endogeneity concerns. Our findings reveal that a 1% increase in land prices leads to a 0.253% rise in carbon emission intensity, driven by heightened financing constraints and reduced innovation. The effects are most pronounced in central and western regions, among non-state-owned enterprises, and in industries with stricter environmental regulations or firms acquiring land through public bidding. These findings highlight critical policy implications: land market reforms to curb speculative price inflation, enhanced access to financing, and targeted support for innovation in high-impact regions and industries. By providing novel insights into the environmental impact of land price dynamics, this research offers practical guidance for balancing economic development and carbon reduction efforts.